RATIONALITY AND CHOICES IN ECONOMICS: BEHAVIORAL AND EVOLUTIONARY APPROACHES - GRAZIANO, Mario; SCHILIRÒ, Daniele (Theoretical and Practical Research in Economic Fields; Vol 2 No 2 (2011): TPREF, Volume II, Issue 2(4), Winter 2011, 2011)
The paper critically discusses the issue of rationality and choices in economics in both the behavioural and evolutionary approaches. Our study aims, on the one hand, to highlight the scientific contributions of psychology in economics, since psychology, and with it the theoretical approach of the behavioral economics, has made more complex and problematic the analysis of economic choices, showing the limits of rationality. On the other hand, the work offers a reinterpretation of the theory of Alfred Marshall in a biological-evolutionary perspective. The reinterpretation of Marshall's theory in a evolutionary perspective aims to show that, historically, economics has not been a discipline aligned in a homogenous way to a single and undifferentiated thought, locked into the idea of perfect rationality, but, on the opposite, is a discipline that has enriched itself and continually is enriching by contributions and significant contaminations with other research fields.